Influence of the low voltage pulsed magnetic field on the columnar-to-equiaxed transition during directional solidification of superalloy K4169. (1st July 2020) - Zhang, Kuiliang; Li, Yingju; Yang, Yuansheng
Abstract: The low voltage pulsed magnetic field (LVPMF) disrupts the columnar dendrite growth, and the columnar-to-equiaxed transition (CET) occurs during the directional solidification of superalloy K4169. Within the pulse voltage ranging from 100 V to 200 V, a transition from columnar to equiaxed grain was observed, and the grain size decreased as the pulse voltage rised. As the pulse frequency increased, the CET occurred, and the grains were refined. However, the grains became coarse, and the solidification structure was columnar crystal again when frequency increased to 10 Hz. The LVPMF had an optimal frequency to promote CET. The LVPMF on the CET was affected by the withdrawal speed and increasing the withdrawal speed enhances the CET. The distribution of electromagnetic force and flow field in the melt under the LVPMF were modeled and simulated to reveal the CET mechanism. It is considered that the CET should be attributed to the coupling effects of magnetic vibration and melt convection induced by the LVPMF.